PERSIAN PRESENCE IN AYUTTHAUYA: Iran–Thailand Relations, Cultural Hybridity, and the Role of Sheikh Ahmad Qomi in Pre-Modern Southeast Asia - Wafi, Mahmud Hibatul; Hidayat, Taufiq; Palawa, Alimuddin Hasan (Asia-Pacific Journal on Religion and Society, 2025)
This study investigates the historical presence and cultural contributions of the Persian community in Ayutthaya, Thailand, with a particular focus on Sheikh Ahmad Qomi as a central figure of Islamic diplomacy, political integration, and transnational cultural exchange in the early 17th century. Drawing on the framework of cultural hybridity (Bhabha) and intra-Asian cosmopolitanism (Duara; Green), the research explores how Persian elements were localized into Thai cultural, political, and aesthetic forms—from Arabesque architectural motifs to the culinary adaptation of Massaman curry. Far from being a passive cultural visitor, Persia played a proactive role in shaping Thailand’s bureaucratic institutions, religious pluralism, and soft power diplomacy. The findings challenge dominant postcolonial narratives that view Southeast Asia merely through the lens of European colonization, advocating instead for a reorientation toward the agency of Asian actors in shaping regional histories. This paper contributes to the growing body of literature that seeks to decolonize Southeast Asian historiography and reinstate the complexity of Asia-Asia cultural dynamics.